1998
DOI: 10.1021/ja9808853
|View full text |Cite
|
Sign up to set email alerts
|

Highly Porous Polyhedral Silsesquioxane Polymers. Synthesis and Characterization

Abstract: Polyhedral octahydridosilsesquioxanes, [HSiO1.5]8 (1) and [(HSiMe2O)SiO1.5]8 (3) were hydrosilylatively copolymerized with stoichiometric amounts of the octavinylsilsesquioxanes, [vinylSiO1.5]8 (2) and [(vinylSiMe2O)SiO1.5]8 (4) in toluene using platinum divinyltetramethyldisiloxane, “Pt(dvs)”, as catalyst. The degree of condensation of the resultant four copolymers ranges from 43% to 81% depending on intercube chain lengths, as determined by solid state 13C and 29Si MAS NMR analyses, using cross-polarization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
377
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 385 publications
(384 citation statements)
references
References 47 publications
5
377
2
Order By: Relevance
“…57 8 , to form cubic silsesquioxane networks connected by tethers with six-atom backbones. Characterization of the networks with nitrogen sorption, positron annihilation lifetime spectroscopy (PALS), and small angle X-ray scattering (SAXS) revealed that the specific surface area and pore volume decreased as the length of the linkers increased.…”
Section: Cross-linked Network Of Octafunctional Possmentioning
confidence: 99%
“…57 8 , to form cubic silsesquioxane networks connected by tethers with six-atom backbones. Characterization of the networks with nitrogen sorption, positron annihilation lifetime spectroscopy (PALS), and small angle X-ray scattering (SAXS) revealed that the specific surface area and pore volume decreased as the length of the linkers increased.…”
Section: Cross-linked Network Of Octafunctional Possmentioning
confidence: 99%
“…POSS with one or more covalently bonded reactive groups is suitable for polymerization, grafting, surface bonding, blending and other transformations to build organic/inorganic hybrid materials at the molecular level. [9][10][11][12][13] POSS functionalized with groups such as hydrogen, 14 amine, 15 vinyl, 16 epoxy 17 and isocyanate 18 can be used as monomers or comonomers in typical polymerizations. One such POSS, hydrogen silsesquioxane (HSQ), has attracted increasing interest in scientific research and technological innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Silsesquioxane based high SSA materials have been synthesized by FriedelCrafts, 43)45) cross-coupling, 41),46) 48) thiol-ene, 49) radical polymerization, 50) polyesters/polyimides, 51),52) and hydrosilylation. 42)53) The best of these materials made by FriedelCrafts reaction was reported by Chaikittisilp et al, in which they have achieved 2500 m 2 /g. 43) However most methods are limited due to their multistep reactions, and use of expensive or large amounts of catalyst.…”
Section: )39)mentioning
confidence: 98%
“…27) 39) Most high surface area materials containing silicon are made via solgel polymerization of tri-and tetraalkoxysilanes. 40) 42) These materials are made by acid or base catalysis through controlled hydrolysis and condensation to form highly crosslinked xero-or aerogels depending on the drying method. Surface areas of >1000 m 2 /g have been achieved by these methods, however the long reaction times necessary and the use of aqueous/polar solvent systems to make these materials by solgel processing has prompted exploration of simple alternative synthetic methods to high surface area materials, especially those that avoid aqueous solutions, use low catalyst loadings (<10 mol %), and can be made within minutes rather than hours or days.…”
Section: )39)mentioning
confidence: 99%